Bimbingan Teknis Penyusunan Laporan Keuangan Pada Koperasi Produsen Pancur Agro Makmur Jalan Candi Penataran XII, Kalipancur RT 03/4 Semarang Jawa-Tengah - Gregorius Anggana L; Listyorini Wahyu Widati; J Jaeni (LPPM STIKOM Tunas Bangsa, 2023)
Accounting is a systematic process for producing financial information that can be used for decision making for its users. Like the Pancur Agro Makmur Producer Cooperative, Semarang City, accounting is needed in the process of recording and reporting its operational activities. Accounting will provide several benefits for cooperatives, including: (1) Cooperatives can find out the company's financial performance, (2) Cooperatives can know the position of funds, both sources and uses, (3) Cooperatives can make appropriate budgets, (4) Cooperatives can calculate taxes, and (5) Cooperatives can find out cash flows during a certain period. The main obstacle faced is that cooperatives find it difficult to use accounting in their business activities. There is currently no literature currently circulating that focuses on cooperative financial management. Another obstacle is that there are many transactions that occur in Cooperatives such as bartering/exchanging services but examples are not provided in the books so that when these transactions occur, the Cooperative prefers not to record them.